Tenascin C levels in patients with mild and severe preeclampsia - Orak, Ugur; Celik, Ebru; Kavak, Salih Burcin; Demirel, Ismail; Atilgan, Remzi; Aydin, Suleyman; Sapmaz, Ekrem (Taylor & Francis Ltd, 2016)
Objective: To determine the serum tenascin-C (TN-C) levels in cases with mild and severe preeclampsia.Methods: Pregnant women were divided into three groups, namely healthy pregnants (Group 1, n=20), pregnants with mild preeclampsia (Group 2, n=20) and pregnants with severe preeclampsia (Group 3, n=20). The groups were formed so as to match each other in terms of gestational week. From each pregnant woman, pre- and post-delivery blood samples were obtained to measure serum TN-C levels. The data were evaluated using the Kruskall-Wallis variance analysis. For the obtained values of p<0.05, the groups were compared in pairs. A p value of <0.017 was accepted as significant.Results: In Groups 1, 2 and 3, the prepartum TN-C levels were 5.020.4 mu g/ml, 12.8 +/- 2.9 mu g/ml and 33.8 +/- 11.7 mu g/ml, and in the postpartum TN-C levels were 4.7 +/- 0.1 mu g/ml, 11.7 +/- 1.8 mu g/ml and 50.6 +/- 33.8 mu g/ml, respectively. There was a significant difference between the groups in terms of the prepartum and postpartum TN-C levels (p<0.017, Mann-Whitney U [MWU] test). There was also a significant difference in the prepartum TN-C levels between Groups 2 and 3 (p<0.017, MWU test).Conclusions: The prepartum and postpartum TN-C levels were significantly higher in mild and severe preeclampsia than those in healthy pregnants.
Keywords: Cytokine; preeclampsia; tenascin-C